2020
DOI: 10.1039/c9sm02392e
|View full text |Cite|
|
Sign up to set email alerts
|

Viscoelastic interfaces comprising of cellulose nanocrystals and lauroyl ethyl arginate for enhanced foam stability

Abstract: At submillimolar concentrations of lauroyl ethyl arginate, cellulose nanocrystals aggregate and form elongated fibres. This interfacial assembly efficiently stabilises foams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 52 publications
5
30
0
Order By: Relevance
“…Bai et al used Mirenat-G containing 10.5% LAE in glycerol, measured the surface tension isotherm and established the CMC value at 0.1%wt (2.4 mM), and the σ CMC around 26 mN/m [ 13 ]. In our recent work, we determined the surface tension isotherm of LAE surfactant (commercial name Mirenat-P/100) with about 90% surfactant content and obtained similar results [ 12 ]. Other authors presented CMC and σ CMC values without reporting the isotherms.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Bai et al used Mirenat-G containing 10.5% LAE in glycerol, measured the surface tension isotherm and established the CMC value at 0.1%wt (2.4 mM), and the σ CMC around 26 mN/m [ 13 ]. In our recent work, we determined the surface tension isotherm of LAE surfactant (commercial name Mirenat-P/100) with about 90% surfactant content and obtained similar results [ 12 ]. Other authors presented CMC and σ CMC values without reporting the isotherms.…”
Section: Introductionmentioning
confidence: 84%
“…Strong binding of LAE to the surface of negatively charged nanoparticles can be used to modify their surface properties for particular applications. For example, ethyl lauroyl arginate was used to modify the cellulose nanocrystals (CNC) for the improvement of foamability and foam stability [ 12 ] or stability of emulsions [ 13 ]. Three types of LAE-CNC interactions were recognised: the electrostatic attraction at low surfactant concentrations, followed by the hydrophobic interaction, and polymer-induced micellisation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Foaming experiments carried out with the double syringe for a commercial brand of LAE (85% purity) showed that at concentrations below 0.35 mM, its solution did not form foams surviving more than several minutes. On the contrary, when mixed with hydrophilic sulfated cellulose nanocrystals, foams could be stable for up to 4 h [21]. Nanometric sCNC with sulfate hydrophilic groups moderately interact with LAE at low surfactant concentrations, and particle zeta potential and hydrodynamic diameter do not change significantly.…”
Section: Of 13mentioning
confidence: 96%
“…Foaming experiments were carried out with the double syringe technique [19][20][21]with two single-use medical syringes of 60 mL volume connected by a narrow tube. First, 20 mL of LAE-CNC solution and 40 mL of air were mixed, and the solution passed from one syringe to the other ten times.…”
Section: Foamingmentioning
confidence: 99%
See 1 more Smart Citation